2015
DOI: 10.1093/mnras/stv2553
|View full text |Cite
|
Sign up to set email alerts
|

DeepChandraobservations of Pictor A

Abstract: We report on deep Chandra observations of the nearby broad-line radio galaxy Pictor A, which we combine with new Australia Telescope Compact Array (ATCA) observations. The new X-ray data have a factor 4 more exposure than observations previously presented and span a 15-year time baseline, allowing a detailed study of the spatial, temporal and spectral properties of the AGN, jet, hotspot and lobes. We present evidence for further time variation of the jet, though the flare that we reported in previous work rema… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
116
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(132 citation statements)
references
References 84 publications
16
116
0
Order By: Relevance
“…w > 2) is inconsistent with our estimates at the 2σ level. The comparison of our dynamical model based jet power and equipartition factor estimates to independent measurements from Hardcastle et al (2016) and Ineson et al (2017) have yielded the same outcome: a proton-to-lepton ratio of w < 2 at the 2σ level. There is therefore strong evidence against an energetically dominant population of relativistic protons or thermal plasma (i.e.…”
Section: Radio Lobe Plasma Compositionsupporting
confidence: 55%
“…w > 2) is inconsistent with our estimates at the 2σ level. The comparison of our dynamical model based jet power and equipartition factor estimates to independent measurements from Hardcastle et al (2016) and Ineson et al (2017) have yielded the same outcome: a proton-to-lepton ratio of w < 2 at the 2σ level. There is therefore strong evidence against an energetically dominant population of relativistic protons or thermal plasma (i.e.…”
Section: Radio Lobe Plasma Compositionsupporting
confidence: 55%
“…Tingay et al (2008) suggested that X-rays in Pictor A are produced by synchrotron emission from compact pc-scale transient regions of enhanced magnetic field. This is consistent also with the recent discovery of temporal variability of the X-ray emission in the hot spot of Pictor A (Hardcastle et al 2016). An important result obtained by our ALMA observations of the hot spot 3C 445 South is the lack of significant polarization between E and W and in the diffuse emission located to the north of the polarized emission and visible up to the optical I-, R-, and B-band (Orienti et al 2012).…”
Section: Discussionsupporting
confidence: 92%
“…Given the relatively small source size, predictions for X-ray inverse-Compton radiation are dominated by the synchrotron self-Compton process, but the field strength would need to be almost 100 times below the equipartition value of 14 nT to match observations, with an implausible increase in total energy. Instead it is more likely that the X-rays are synchrotron, as inferred to be common in jet knots of FR I radio galaxies , found not unusual in FR II radio galaxies (e.g., Kraft et al 2005;Kataoka et al 2008;Hardcastle et al 2016), and favoured for some quasar jets (e.g., Jester et al 2007;Cara et al 2013;Meyer et al 2015). The precise characteristics of the radio to X-ray spectrum cannot be determined in the absence of high-resolution observations at intermediate frequencies, but we can infer that the spectral break needs to be ∆α > 0.5 to accommodate the measured value of αr and the interpolated value of αrx, and ∆α = 0.7 is adopted in Figure 10.…”
Section: Jet Knotmentioning
confidence: 98%